(untitled) (World Bulletin of Public Health, 2022)
In this article to summarize the data on the features of hand injuries in patients with polytrauma. The rate of the hand and wrist injuries is about 25 % among patients with poly trauma. Damages of the hand in polytrauma are commonly featured by severe soft tissue injury and multiple fractures of the bones due to high energy of a traumatic agent in the road accidents or catatrauma. Treatment of life-threatening injuries is a primary objective in patients with polytrauma, whereas treatment of "small fractures" is carried out after all the others. Late diagnostics and untimely initiation of treatment can cause the hand defunctionalization